IMPROVEMENT OF PADDLES IN ORDER TO INCREASE THE LEVEL OF COTTON DRYING IN THE 2SB-10 DRUM DRYER (Journal of Science-Innovative Research in Uzbekistan, 2024)
The 2SB-10 type of drying drum used in cotton ginning enterprises reduces its air consumption by installing paddles at an angle of 80 degrees in the middle